Analisis Kedudukan Akal Perspektif Hamka - Syaiful Dinata (UIN Sulthan Thaha Saifuddin Jambi, 2024)
A study of the position of reason needs to be carried out in order to be able to distinguish between right and wrong, and good and bad. Many previous Muslim figures who provided sheets of their writings discussed the intricacies and problems of reason. However, the issue of the position of reason is still being discussed around certain issues, especially in Islamic thematic issues. This fact is of course very concerning, because an issue as important as reason should not escape serious discussion. The problem in this research is how to describe the position of reason in Hamka's perspective. The purpose of this study is to analyze the position of reason from the perspective of Hamka. By using a descriptive qualitative research method, the findings of this study illustrate that the position of reason from the perspective of Hamka, namely the position of reason is an important thing in human life, because it is the determinant of good and evil. Reason is the ability to think that is in human beings, and is also explained as a manifestation or embodiment of one's soul. According to Hamka reason is a bond, meaning that with the position of reason in the human soul, it will keep people from following seductions, traps, even the shackles of lust.